2009
DOI: 10.1007/s10895-009-0504-9
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Interaction and Determination of Calf Thymus DNA with Two Ethidium Derivatives

Abstract: In this paper, we reported the syntheses and investigation of the modes of binding to DNA of the two new ethidium derivatives containing benzoyl and phenylacetyl groups of both amines at 3-and 8- positions. The interactions between calf thymus DNA (ct-DNA) and the two derivatives, 3,8-dibenzoylamino-5-ethyl-6-phenylphenantridinium cloride (E2) and 3,8-diphenylacetylamino-5-ethyl-6-phenylphenantridinium chloride (E3), were investigated by fluorescence quenching spectra and UV-vis absorption spectra. The Stern-V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The intercalative and groove binding modes are more effective to block DNA replication than that of electrostatic interaction. 44 It has been revealed that when using an anionic quencher, the DNA base pairs around the intercalators hinder the accessibility of the fluorescent probe to the quencher. However, the use of electrostatic repulsion between the anionic quenchers and DNA phosphate backbones can be beneficial for the intercalated species.…”
Section: Biological Evaluation and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intercalative and groove binding modes are more effective to block DNA replication than that of electrostatic interaction. 44 It has been revealed that when using an anionic quencher, the DNA base pairs around the intercalators hinder the accessibility of the fluorescent probe to the quencher. However, the use of electrostatic repulsion between the anionic quenchers and DNA phosphate backbones can be beneficial for the intercalated species.…”
Section: Biological Evaluation and Discussionmentioning
confidence: 99%
“…It is generally accepted that small molecules have three binding modes with DNA by noncovalent interactions, including intercalation with base pairs, groove binding, and electrostatic interaction with the anionic sugar phosphate backbone. The intercalative and groove binding modes are more effective to block DNA replication than that of electrostatic interaction …”
Section: Biological Evaluation and Discussionmentioning
confidence: 99%
“…The quenching effect shows a good adjustment to the Stern-Volmer equation with K SV constants of 8.4 x 10 6 and 4.6 x 10 6 . Studies concerning temperature on the quenching effect showed that K SV decreased when temperature was increased and the authors suggest a static mechanism for the quenching (Akbay et al, 2009). Other studies concerning the interaction of ethidium bromide analogues with DNA have shown that the presence of weak electron-donating substituents on phenantridinium moiety favours a significant fluorescence quenching (Prunkl et al, 2010).…”
Section: Fluorescence Emission Spectroscopymentioning
confidence: 95%
“…EtBr and EtBr-polynucleotide complexes fluorescence was recorded at 610 nm (excitation at 540 nm). 12,15,16 The adsorption isotherms in Schatchard's coordinates were obtained as described in the literature.…”
Section: Methodsmentioning
confidence: 99%